2012
DOI: 10.1177/0960327112459533
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of rat plasma following chronic low-dose exposure to dichlorvos

Abstract: This study aims to assess the metabolomic profile and related histopathological outcomes of rat plasma after chronic low-dose exposure to dichlorvos (DDVP). A total of 120 male Wistar rats were treated with 0, 2.4, 7.2, and 21.6 mg/kg of body weight/day DDVP continuously for 24 weeks by drinking water. Rat plasma samples were collected at different time-points to measure the metabolomic profiles by ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). Liver tissue analysis was performed to corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Metabonomics as a new technical platform has been widely used in toxicology. [21][22][23] In our study, PCA score plot and PLS-DA score plot showed clear separation between ASB-treated and control groups, which indicated that urine metabolic pattern significantly changed after the treatment of ASB.…”
Section: Discussionsupporting
confidence: 57%
“…Metabonomics as a new technical platform has been widely used in toxicology. [21][22][23] In our study, PCA score plot and PLS-DA score plot showed clear separation between ASB-treated and control groups, which indicated that urine metabolic pattern significantly changed after the treatment of ASB.…”
Section: Discussionsupporting
confidence: 57%
“…Our findings may also be in line with previous observations of higher plasma levels of type II PLA2 in sepsis patients, which significantly correlated with TNF-α, IL-6 and IL-8 levels [ 47 ]. On the other hand, elevated plasma levels of LysoPE (16:0/0:0) have been observed in rats with induced-liver injuries as a result of massive destruction of cell membranes [ 48 , 49 ]. Therefore, it is also possible that the high LysoPE levels may be the consequence of severe organ damage during systemic melioidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, metabonomics has been widely applied in many research areas, including the chemical safety of food, drug toxicology, biomarker discovery, functional genomics, and molecular pathology. 20,21 In our previous study, Yang et al 22 analyzed the toxic effects of exposure to low-level DDVP on rat plasma using ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). The results showed that lysoPC (15:0/0:0), lysoPC (16:0/0:0), lysoPC (17:0/0:0), lysoPC (0:0/18:0), sphingosine, sphinganine, C16 sphinganine, C17 sphinganine, and arachidonic acid (AA) significantly decreased while lysoPE (16:0/0:0) significantly increased in the DDVP-treated group compared with the control group.…”
Section: Introductionmentioning
confidence: 99%